Molecular Modeling Study on Diazine Indole Acetic Acid Derivatives for CRTH2 Inhibitory Activity - Babu, Sathya; Rupa, Mottadi; Kumar Nagarajan, Santhosh; Sohn, Honglae; Madhavan, Thirumurthy (Combinatorial Chemistry & High Throughput Screening, 2016)
In the present work, molecular modeling studies have been reported on a series of diazine indole acetic acid derivatives to analyze the structure-activity relationship studies of CRTH2 using fragment (Topomer CoMFA and HQSAR) and field (CoMFA and CoMSIA) based QSAR methods. Twenty-six compounds were used as a training set to establish the model, and six compounds were used as a test set to validate the model. The generated models exhibited good statistical results such as correlation coefficient (r2) and the cross-validated correlation coefficient (q2). Topomer CoMFA analysis yielded the q2 of 0.610 and r2 of 0.981. HQSAR model generated using bond and connectivity as fragment distinction and 3-6 as fragment size has the q2 value of 0.707 and conventional r2 value of 0.892 with five components. CoMFA model was assessed by cross-validated q2 value of 0.543 and r2 value of 0.901 with steric and electrostatic fields. CoMSIA model generated using steric, hydrophobic and donor fields with q2 value of 0.550 and r2 value of 0.888 was found to be the optimal model among the various models generated. The contour maps were generated to analyze the important structural features that regulate their inhibitory potency. From the result of contour maps we have suggested the critical sites for chemical modification which will be useful in designing potent compounds with improved activity.
Keywords: Topomer CoMFA